IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PENGURANGAN PEKERJA ANAK DI INDONESIA PADA MASA PANDEMI COVID-19 (2020-2021) - Regina Gabriella Memah; Putri Hergianasari; Sri Suwartiningsih (Yayasan Literasi Sains Indonesia, 2022)
Child laborers are children who are forced to do routine work for their parents to meet their daily needs at home. This can be caused by the poverty of families who have very low incomes or do not have jobs. The entry of the Corona virus in Indonesia in 2020, greatly affected people's activities so that it had to blend in with new government policies to prevent the spread of Covid-19. The existence of a pandemic in 2020, there are many impacts experienced by the community, including those who are unable to send their children to school. The need for implementing policies from the government to prevent an increase in the number of child labor in Indonesia during the Covid-19 pandemic. Therefore, this study will use the theory of Constructivism according to Jean Piaget and use the qualitative method in discussing the implementation of government policies on reducing child labor in Indonesia during the Covid-19 pandemic. With the implementation carried out by the government during the Covid-19 pandemic in 2020, the number of child laborers will decrease in 2021, so that with the efforts of the government the number of child labor can decrease slowly in accordance with the government's expectations.